Modelling trait and state willingness to communicate in a second language: An experience sampling approach - Lee, Ju Seong; Chiu, Ming Ming (Studies in Second Language Learning and Teaching, 2024)
This study investigates whether demographics, L2 enjoyment, L2 anxiety, psychological well-being, or Informal Digital Learning of English (IDLE) affected willingness to communicate in L2 (L2 WTC) at trait and state levels. Across two weeks, 16 Hong Kong EFL students completed pre-and post-trait-level surveys and generated 1,120 state-level responses via the experience sampling method (ESM). The survey findings revealed that students who were older, had higher language proficiency, or had higher pre-WTC digitally reported higher L2 WTC in the classroom. Students who studied English longer, had higher language proficiency, had higher pre-psychological well-being, had a higher standard deviation L2 WTC over 14 days, or had higher teacher appreciation showed higher L2 WTC outside of class. Students with higher language proficiency, higher pre-WTC digitally, or higher post-psychological well-being reported higher L2 WTC in digital settings. The ESM findings revealed that students with higher teacher appreciation, currently engaged in productive IDLE or both receptive and productive types of IDLE, currently experienced greater L2 enjoyment, or currently experienced greater well-being had higher L2 WTC now. Our findings contribute to (a) L2 WTC, informal language learning, and positive psychology theories, and (b) teachers’ strategies to enhance students’ L2 WTC overall and in the moment.